Nanophthalmos patient with a THR518MET mutation in MYRF, a case report - Hagedorn, Joshua (BMC Ophthalmol, 2020)
BACKGROUND: Nanophthalmos has a significant genetic background and disease-causing mutations have been recently been reported in the myelin regulatory factor (MYRF) gene. We report clinical features in a patient with nanophthalmos and a Thr518Met MYRF mutation. CASE PRESENTATION: A three-year-old male was discovered to have nanophthalmos after first presenting to the emergency department for a frontal headache, eye pain, emesis, and lethargy. Imaging studies (CT and MRI) were negative except for increased posterior fossa cerebrospinal fluid. Subsequent examinations revealed nanophthalmos (short axial eye lengths 18.1 mm OD and 18.3 mm OS), microcornea, and a large crystalline lens. Peripheral chorioretinal pigment abnormalities were also observed. He experienced episodes of marked ocular hypertension (53 mmHg OD and 60 mmHg) likely due to intermittent angle closure precipitated by nanophthalmos. The ocular hypertension was responsive to topical medicines. Genetic analysis of known nanophthalmos genes MFRP and TMEM98 were negative, while a novel mutation, Thr518Met was detected in MYRF. The Thr518Met mutation was absent from 362 matched normal controls and was extremely rare in a large population database, allele frequency of 0.000024. The Thr518Met mutation altered a highly conserved amino acid in the MYRF protein and three of four algorithms suggested that this mutation is likely pathogenic. Finally, molecular modeling showed that the Thr518Met mutation is damaging to MYRF structure. Together these data suggest that the Thr518Met mutation causes nanophthalmos. CONCLUSIONS: Nanophthalmos may present at an early age with features of angle closure glaucoma and a Thr518Met mutation in MYRF was detected in a patient with nanophthalmos. Prevalence data, homology data, mutation analysis data, and protein modeling data suggest that this variant is pathogenic and may expand the phenotypic range of syndromic nanophthalmos caused by MYRF mutations to include central nervous system abnormalities (increased posterior fossa cerebrospinal fluid).